(untitled) (SCIÉNDO INGENIUM, 2021)
The objective was to genotypically determine by PCRc, the presence of the blaSHV, blaTEM and blaCTX-M genes, in K. pneumoniae producer of ESBL, of the ICU service of two hospitals in Cajamarca. In this study, different clinical biological samples were used, from which 59 strains of K. pneumoniae ESBL + were isolated, of which 37 (62.7%) strains correspond to the Regional Hospital of Cajamarca and 22 (37.3%) to the Hospital II Essalud Cajamarca. With respect to the production of resistance genes, in the Regional Hospital of Cajamarca 37/37 (100%) strains presented the blaSHV gene, 33/37 (89%) the blaTEM gene and 36/37 (97%) the blaCTX- M. In the Essalud Cajamarca II hospital, the presence of the blaSHV gene was 17/22 (77%) strains, blaTEM 20/22 (91%) and blaCTX-M 20/22 (91%). Performing the total statistical analysis at the level of hospitals of Cajamarca, the blaSHV gene is present in 54/59 (92%) of strains, the blaTEM gene in 53/59 (90%) and the blaCTX-M gene in 56/59 (95%) strains. It is therefore concluded that, in both hospitals of Cajamarca, antimicrobial resistance is high, which is mainly produced by the genes under study, especially for K. pneumoniae ESBL +, which encode extended spectrum beta-lactamases